Tracing controversies in hacker communities: ethical considerations for internet research. Issue 1 (2nd January 2020) - Richterich, Annika
ABSTRACT: This paper reflects on the ethics of internet research on community controversies. Specifically, it focuses on controversies concerning gendered, social interaction in hacking communities. It addresses the question how internet researchers should treat and represent content that individuals controversially discussed online. While many internet sources are likewise technically public, they may yet suggest distinct privacy expectations on the part of involved individuals. In internet research, ethical decision-making regarding which online primary sources may be, e.g., referenced and quoted or require anonymisation is still ambiguous and contested. Instead of generalisable rules, the context dependence of internet research ethics has been frequently stressed. Given this ambiguity, the paper elaborates on ethical decisions and their implications by exploring the case of a controversial hackerspaces.org mailing list debate. In tracing data across different platforms, it analyses the emerging ethico-methodological challenges.